Fast Algorithm for Selective Image Segmentation Model - K Jumaat, Abdul; Chen, Ke (International Journal of Engineering and Technology, 2018)
Selective image segmentation model aims to separate a specific object from its surroundings. To solve the model, the common practice to deal with its non-differentiable term is to approximate the original functional. While this approach yields to successful segmentation result, however the segmentation process can be slow. In this paper, we showed how to solve the model without approximation using Chambolleâ€™s projection algorithm. Numerical tests show that good visual quality of segmentation is obtained in a fast-computational time.Â Â